1980
DOI: 10.4319/lo.1980.25.1.0012
|View full text |Cite
|
Sign up to set email alerts
|

Buffering of silica and phosphate in a turbid river1

Abstract: The buffering of riverine dissolved silica and phosphate by sorption reactions between the aqueous phase and suspended secliment is examined with the turbid Colorado River system as a model. Concentrations are found to lie in a range predicted from laboratory sorption experiments with natural sediments and waters. Phosphate is probably highly buffered by suspended sediment during river flow while silica is not. Silica appreciably affects phosphate sorption reactions but not vice versa. Increased temperature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 19 publications
(23 reference statements)
5
50
1
Order By: Relevance
“…This potential was evidenced by the higher phosphorus content of the agricultural stream sediments (Table 6). Mayer and Gloss ( 1980) found through repeated desorption studies that sediments can supply significantly more phosphorus than is indicated by EPC values. This phosphorus would be released from the sediments in the presence of agents like bacteria and algae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential was evidenced by the higher phosphorus content of the agricultural stream sediments (Table 6). Mayer and Gloss ( 1980) found through repeated desorption studies that sediments can supply significantly more phosphorus than is indicated by EPC values. This phosphorus would be released from the sediments in the presence of agents like bacteria and algae.…”
Section: Discussionmentioning
confidence: 99%
“…The river velocity and nutrient concentration influence the diffusion rate. For phosphorus, the concentration in stream water is to a large extent controlled by the sediments through sorption-desorption processes (Meyer 1979;Mayer and Gloss 1980;Hill 1982). Factors such as sediment particle size, iron, aluminum, and organic content (Syers et al 1973;Meyer 1979;Hill 1982) influence phosphorus sorption by river sediments.…”
mentioning
confidence: 99%
“…At this point on a buffer diagram, phosphate is neither adsorbed from solution to the sediment nor desorbed from the sediment to solution and is often interpreted as the equilibrium condition of natural systems (Siever & Woodford, 1973: McCallister & Logan, 1978Mayer & Gloss, 1980). In this study, the EPC for individual fractions of summer sediment ranged from 15 to 80 [xg P I" 1 and indicated typical ranges of phosphate buffering by sediment in these rivers.…”
Section: Phosphate Sorption Of Individual Size Fractionsmentioning
confidence: 91%
“…That is, phosphorous levels in the water column may be controlled by sediment interactions rather than external sources. Lake sediments can act as either a source or a sink for phosphorous in the water column depending on the amount of dissolved oxygen, water column phosphorus concentrations, and sediment phosphorous concentrations [13].…”
Section: Phosphorousmentioning
confidence: 99%